2019
DOI: 10.1111/vox.12796
|View full text |Cite
|
Sign up to set email alerts
|

Why do young men lapse from blood donation?

Abstract: Background and Objectives Most men have larger blood volumes and iron stores, making them more suitable blood donors; however, women dominate the donor population in Stockholm. Motives for cessation and returning were examined in a group of lapsing young male donors, in order to improve retention. Methods Demographic studies of the donor population. An online survey was sent to 1012 lapsing male donors aged 18–35 years. Questions focused on reasons for lapsing, returning and donor motivation. Results Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
(57 reference statements)
2
21
1
3
Order By: Relevance
“…This observation contrasts with the results of several analyses that have reported higher male return rates 30–33 . This difference in results may be due to different screening and eligibility criteria between men and women in Australia compared with other countries (such as, a longer inter‐donation intervals for women) 21 . Further, a lower participation in blood donation by women may be caused by a higher deferral rate for anaemia or iron‐deficiency, 34,35 pregnancy and breastfeeding, 6,9,30,35 and higher rates of donation related anxiety and vasovagal reactions 34,36 .…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This observation contrasts with the results of several analyses that have reported higher male return rates 30–33 . This difference in results may be due to different screening and eligibility criteria between men and women in Australia compared with other countries (such as, a longer inter‐donation intervals for women) 21 . Further, a lower participation in blood donation by women may be caused by a higher deferral rate for anaemia or iron‐deficiency, 34,35 pregnancy and breastfeeding, 6,9,30,35 and higher rates of donation related anxiety and vasovagal reactions 34,36 .…”
Section: Discussioncontrasting
confidence: 84%
“…7 The impact of this can be compounded by other life-related events disproportionately experienced by younger donors such as starting a new job and moving to another place, 9,20 which can also deter return and regular donation. Further, younger donors who come back to donate are also likely to disproportionately experience deferrals due to lifestyle related reasons (such as tattoos, travel etc), low iron levels or anaemia, 2,[19][20][21] and vasovagal reactions, 22 all of which can further increase risk of lapse. [23][24][25] Consistent with several other analyses, 16,26,27 donors starting to donate when aged 30 and above were the most productive in our cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male donors are statistically more robust to the demands of blood donation. On average they have greater iron stores, a larger blood volume and larger veins [1]. Moreover, they are less likely than female donors to report vasovagal reactions from donating [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 70% of the non‐willing donors cited time constraints for not donating again, the rest of the donors did not give any specific answers. Previous studies have shown that one of the main factors cited for low donor return rates is time constraints 18,19 …”
Section: Discussionmentioning
confidence: 99%